A Case of Lymphocytic Myocarditis with Eosinophilic Degranulation Successfully Treated with Steroid Therapy - Tomoko Inoue; Fusako Sera; Shunsuke Nishimura; Kei Nakamoto; Yasumasa Tsukamoto; Isamu Mizote; Tomohito Ohtani; Shungo Hikoso; Yoshihiko Ikeda; Yumiko Hori; Hatsue Ishibashi-Ueda; Eiichi Morii; et al. (Case Reports in Cardiology)
A 49-year-old woman was admitted with suspicion of acute myocarditis. On the next day after admission, her serum troponin I level continued to rise, indicating progression of myocardial damage. Moreover, her symptoms persisted, and left ventricular ejection fraction did not improve. Because of a predominant infiltration of lymphocytes in the myocardial specimens, lymphocytic myocarditis was diagnosed. However, a close observation of the specimens revealed eosinophil degranulation. Based on this finding, intravenous steroid therapy was initiated. High-dose methylprednisolone led to rapid and appreciable improvements in symptoms and left ventricular function within 12 hours after the first administration, which was followed by normalization of serum troponin I level. Steroid therapy was switched to oral administration and tapered carefully. There was no recurrence of left ventricular dysfunction or elevation of serum troponin I level. In eosinophilic myocarditis, eosinophil degranulation has been recognized as an important finding associated with progression of inflammation and myocardial damage. However, no attention has been paid to the presence and clinical implications of eosinophil degranulation in lymphocytic myocarditis. This case indicates that eosinophil degranulation in lymphocytic myocarditis may be an important finding associated with a high therapeutic response to steroid therapy.